Excessive premature mortality among children with cerebral palsy in rural Uganda: a longitudinal, population-based study - Mortality data of population based CP cohort from Iganga/Mayuge, Uganda - Forssberg, Hans; Kakooza-Mwesige, Angelina (Karolinska Institutet, 2021)
Background
Studies from high-income countries reported reduced life expectancy in children with cerebral palsy (CP), while no population-based study has evaluated mortality of children with CP in sub-Saharan Africa. This study aimed to estimate the mortality rate (MR) of children with CP in a rural region of Uganda and identify risk factors and causes of death (CODs).
Methods and Findings
This population-based, longitudinal cohort study was based on data from Iganga-Mayuge Health and Demographic Surveillance System in eastern Uganda. We identified 97 children (aged 2–17 years) with CP in 2015, whom we followed to 2019. They were compared with an age-matched cohort from the general population (n=41 319). MRs, MR ratios (MRRs), hazard ratios (HRs), and immediate CODs were determined.
MR was 3952 per 100 000 person years (95% CI 2212–6519) in children with CP and 137 per 100 000 person years (95% CI 117–159) in the general population. Standardized MRR was 25·3 in the CP cohort, compared with the general population. In children with CP, risk of death was higher in those with severe gross motor impairments than in those with milder impairments (HR 6·8; p=0·007) and in those with severe malnutrition than in those less malnourished (HR=3·7; p=0·052). MR was higher in females in the CP cohort, with a higher MRR in females (53·0; 95% CI 26·4–106·3) than in males (16·3; 95% CI 7·2–37·2). Age had no significant effect on MR in the CP cohort, but MRR was higher at 10–18 years (39·6; 95% CI 14·2–110·0) than at 2–6 years (21·0; 95% CI 10·2–43·2). Anaemia, malaria, and other infections were the most common CODs in the CP cohort.
Conclusions
Risk of premature death was excessively high in children with CP in rural sub-Saharan Africa, especially in those with severe motor impairments or malnutrition. While global childhood mortality has significantly decreased during recent decades, this observed excessive mortality is a hidden humanitarian demand that needs to be addressed.

The dataset contains of the following files:
- CP_cohort–Children_and_youth_at_the_IM-HDSS.csv
- CoD–General_population_of_children_and_youth_IM-HDSS.csv
- Variable_list.pdf

Details about the variables in the tables can be found in the variable list.

Denna studie har undersökt dödligheten hos barn med CP i en lantlig del av Uganda och identifierat riskfaktorer och dödsorsak.
Vi har följt 97 barn med CP mellan 2–17 år sedan 2015. De jämfördes med en åldersmatchad kohort av 41 319 barn från den allmänna befolkningen. Dödligheten var 3952 per 100 000 personer/år (95% CI 2212–6519) hos barn med CP och 137 per 100 000 personer/år (95% CI 117–159) i den allmänna populationen. Dödligheten var 25·3 gånger högre i CP gruppen. Risken att dö var större hos barn med svår nedsättning av motoriska funktioner jämfört med dem med mildare (HR 6·8; p=0·007). Risken att dö var också större hos dem med uttalad undernäring jämfört med dem med mildare former (HR=3·7; p=0·052). Anemi, malaria, och andra infektioner var den vanligaste dödsorsaken.

En utförligare beskrivning finns i den engelska versionen av katalogposten.

Datasetet består av följande filer:
- CP_cohort–Children_and_youth_at_the_IM-HDSS.csv
- CoD–General_population_of_children_and_youth_IM-HDSS.csv
- Variable_list.pdf

Mer information om variablerna i de olika tabellerna finns i variabel-listan.
Excessive premature mortality among children with cerebral palsy in rural Uganda: a longitudinal, population-based study - Mortality data of population based CP cohort from Iganga/Mayuge, Uganda
Keywords: cerebral palsy; cerebral pares; mortality; mortalitet; children and youth; barn och ungdomar; low and middle income countries; låg och medelinkomstländer; Medical and Health Sciences; Medicin och hälsovetenskap; Clinical Medicine; Klinisk medicin; Pediatrics; Pediatrik; Health Sciences; Hälsovetenskap; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin